ANALISIS FAKTOR YANG MEMPENGARUHI KUALITAS AUDIT - Yoga Putra Meyditiya; Fauziyah Fauziyah; Nur Rahmanti Ratih (Jurnal Ilmiah Manajemen dan Akuntansi, 2025)
This study aims to examine the influence of firm size, audit fees, audit tenure, audit committee, and auditor switching on the quality of audits. The research employs a quantitative method, using secondary data sourced from annual reports of companies in the transportation and logistics sector listed on the Indonesia Stock Exchange for the period of 2021–2023. The sample was selected using purposive sampling, resulting in 23 companies and yielding 69 observational data points. After eliminating one outlier, the final dataset comprised 68 observations. The results reveal that firm size, audit fees, audit tenure, and auditor switching do not significantly affect audit quality. However, the audit committee variable shows a significant impact on audit quality. Furthermore, collectively, all the independent variables is firm size, audit fees, audit tenure, audit committee, and auditor switching are found to influence audit quality.